2013
DOI: 10.1248/bpb.b13-00494
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Mechanism by Which <i>Gypsum fibrosum</i>, a Traditional Chinese Medicine, Maintains Cutaneous Water Content

Abstract: Aquaporin-3 (AQP3) plays an important role in maintaining the normal water content of the skin. Previously, we revealed that the expression of cutaneous AQP3 increased following oral administration of Gypsum fibrosum (main component: CaSO 4 ) to mice. The purpose of this study is to elucidate the mechanism by which Gypsum fibrosum increases the expression of cutaneous AQP3 in a keratinocyte cell line. Gypsum fibrosum or CaSO 4 was added to keratinocytes, and the expression level of AQP3, the Ca concentration, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…TCM II was composed of four dried herbs; Cortex Phellodendri , Gypsum Fibrosum , Rhizoma Atractylodes , and Agastache Rugosa . Among these herbs, C. Phellodendron and G. Fibrosum play an important role on clearing heat (Lu et al, 2006; Ikarashi et al, 2013), as well as A. Rugosa and R. Atractylodes are damp-clearing medicines (Yan et al, 2006). It was also reported that the effects of these TCM decoctions in vitro enhanced the antioxidant status and reduced lipid peroxidation in heat-stressed intestinal crypt-like epithelial cells (Guo et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…TCM II was composed of four dried herbs; Cortex Phellodendri , Gypsum Fibrosum , Rhizoma Atractylodes , and Agastache Rugosa . Among these herbs, C. Phellodendron and G. Fibrosum play an important role on clearing heat (Lu et al, 2006; Ikarashi et al, 2013), as well as A. Rugosa and R. Atractylodes are damp-clearing medicines (Yan et al, 2006). It was also reported that the effects of these TCM decoctions in vitro enhanced the antioxidant status and reduced lipid peroxidation in heat-stressed intestinal crypt-like epithelial cells (Guo et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…GF was clearly shown to cause an increase in the intracellular Ca 2+ concentration, PKC activity, and the phosphorylation levels of ERK and CREB, resulting in increased AQP3 expression in keratinocytes (Fig. ) . In addition, it is possible that the effect of GF is attributable to CaSO 4 , given that the mechanisms of action of GF and CaSO 4 were nearly identical.…”
Section: Mechanism Of Skin Aqp3 Expression Increase By Gypsum Fibrosummentioning
confidence: 94%
“…When GF extract was added to human keratinocytes, increased AQP3 expression, increased intracellular Ca 2+ content, elevated PKC activity, and enhanced CREB and ERK phosphorylation were observed . Moreover, it was found that the increase in AQP3 expression upon the addition of GF extract was almost completely suppressed by pretreatment with an inhibitor of PKC activation.…”
Section: Mechanism Of Skin Aqp3 Expression Increase By Gypsum Fibrosummentioning
confidence: 94%
See 2 more Smart Citations